Business Education a Panacea for Unemployment Among Youth in Nigeria - Umar B. , Yusuf; Abdulmumini, H.; Bello, A; Abdullahi, M., Rasheed; Adamu, Zainab (Kashere Journal of Education, 2021)
The teaching of Business Education has been going in to extinction as if the subject has no importance to the youth’s employment in Nigeria. Having recognized teaching of Business Education as vanguard and elements of salvaging the current unemployment rate in Nigeria, the need to have the knowledge of Business Education is considered paramount. This paper intended to highlight the relevance of Business Education as panacea for unemployment among youths in Nigeria. The study therefore, brought to the light of relevance of Business Education, development of Business Education as well as challenges facing Business Education in Nigeria. Finally, the paper forwarded some of the recommendations in promoting Business Education in Nigeria which among others include the need of equipping Business Education Department with adequate and quality teachers with necessary materials such as model rooms, typing pools and computer lab to promote teaching and learning of the subject.